Hermeneutics and nursing care to patients with a tumor wound: a philosophical reflection - Patrícia Lima Queiroz; Janaína de Jesus Castro Câmara; Santana de Maria Alves de Sousa; Helder Machado Passos (Revista de Enfermagem da Universidade Federal de Santa Maria, 2015)
Aim: to reflect on the knowledge and practice of nursing care to patients with a tumor wound, under the philosophical hermeneutics of Gadamer. Method: this is a reflective study. Results: the dynamic interplay between scientific knowledge and the empirical is desirable and even necessary. The philosophy reveals that the practice of doing and acting efficiently and effectively correlates with the technique, and presents the relationship deterioration between theory (knowledge) and practice (doing) under the conditions of modern science. The nurse often takes care of neoplastic wound of a patient from life experiences and professional experiences, being expressed by a dialogical character. Dialogue is the obvious device in the hermeneutical thought of Gadamer. Conclusion: the hermeneutical thought of Gadamer and philosophical foundation of knowledge bring contributions to the care relationship between nurse and patient with tumor wound